OTC premia - Cenedese, Gino; Ranaldo, Angelo; Vasios, Michalis (Journal of Financial Economics, 2020)
Using unique data at transaction and identity levels, we provide the first systematic study of interest rate swaps traded over the counter (OTC). We find substantial and persistent heterogeneity in derivative prices consistent with a pass-through of regulatory costs on to market prices via so-called valuation adjustments (XVA). A client pays a higher price to buy interest rate protection from a dealer (i.e., the client pays a higher fixed rate) if the contract is not cleared via a central counterparty. This OTC premium decreases by posting initial margins and with higher buyer’s creditworthiness. OTC premia are absent for dealers suggesting bargaining power.